Counting solutions to diagonal congruences and Diophantine inequalities - Wilson, Kathryn (My University, 2025)
This dissertation will cover three results. Each result has a connection to Waring's problem and the circle method. Throughout, let p be prime, and let n, k and s be positive integers . . . See PDF file for full abstract.
Keywords: Waring number; Diophantine inequalities; Hardy-Littlewood circle method; Function fields; Congruences; Davenport-Heilbronn method